1978
DOI: 10.1126/science.684421
|View full text |Cite
|
Sign up to set email alerts
|

Plutonium in Drinking Water: Effects of Chlorination on Its Maximum Permissible Concentration

Abstract: Soluble plutonium is oxidized to the Pi(VI) oxidation state by chlorine during water treatment. Under certain conditions Pi(VI) is readily absorbed from the gastrointestinal tract. It appears that due consideration has not been given to the effect that the presence of plutonium in this oxidation state may have on the maximum permissible concentration of plutonium in drinking water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

1980
1980
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 3 publications
0
6
0
2
Order By: Relevance
“…They have shown that dissolved Pu is present as Pu(V) and Pu(VI) under atmospheric conditions. Larsen and Oldham (1978) showed that approximately 70-90% of Pu was present as Pu(VI) in chlorinated drinking waters. Dissolved Pu in neutral and basic brines is present as Pu(VI) (Nitsche et al, 1994).…”
Section: Introductionmentioning
confidence: 98%
“…They have shown that dissolved Pu is present as Pu(V) and Pu(VI) under atmospheric conditions. Larsen and Oldham (1978) showed that approximately 70-90% of Pu was present as Pu(VI) in chlorinated drinking waters. Dissolved Pu in neutral and basic brines is present as Pu(VI) (Nitsche et al, 1994).…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, Sullivan (1980a, b) indicated that smaller particle sizes give largerf, values due to easier digestion in the GI tract. Larsen et al (1977Larsen et al ( , 1983 suggested a f i value for plutonium between and 2X 10-1 based on the chemistry of plutonium in chlorinated drinking water. However, animal studies have not produced convincing evidence that either the oxidation state of the ingested compound or individual biology influence the f l value (NEA 1988).…”
Section: Other Studiesmentioning
confidence: 99%
“…Grâce à ces différentes techniques, on a pu déterminer que le plu tonium des grands lacs américains et de la mer d'Irlande étaient à l'état VI au niveau de l'eau, à l'état IV dans les sédiments [45]. La chloruration des eaux conduit à l'état VI [31]. A Eniwetok, le plutonium est à l'état V et VI dans les eaux du lagon [7].…”
Section: Caractérisation Des éTats De Valenceunclassified
“…Pu4+ : Cet état de valence s'hydrolyse même en milieu très acide, la première réaction d'hydrolyse Pu4+ + H20 H PuOH3+ + H+ débute dès que le pH est supérieur à 0. La valeur moyenne des premières mesures de pK pour cette réaction est d'environ 1,6 [31]. A forte concentration, il est difficile de mesurer les espèces suivantes car, très rapidement, les espèces monomériques s'agrègent pour former des polymères de grande taille où les ions Pu sont liés entre eux par des ponts hydroxo ou oxo [25].…”
Section: Hydrolyse Et Complexationunclassified